XPS study of the corrosion protection of fluorozirconate glasses dip-coated with SnO2 transparent thin films - Rizzato, A. P.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Messaddeq, Younes [UNESP]; Hammer, Peter [UNESP] (Springer, 2004)
Tin oxide nanoparticles prepared by an aqueous sol-gel method were deposited by dip-coating on fluorozirconate glass, ZBLAN (53%ZrF4-20%BaF2-4%LaF3-3%AlF3-20%NaF) to improve its resistance against wet corrosion. The aqueous leaching of uncoated and SnO2-coated fluorozirconate glass was studied by X-ray photoemission spectroscopy (XPS) and it was shown that even an ultra thin tin dioxide film provides good protection of the glass surface against the bulk propagation of the hydrolytic attack.
Keywords: corrosion protection; dip-coating thin film; XPS; tin oxide; ZBLAN